2007
DOI: 10.1128/jb.00904-06
|View full text |Cite
|
Sign up to set email alerts
|

Abortive Phage Resistance Mechanism AbiZ Speeds the Lysis Clock To Cause Premature Lysis of Phage-Infected Lactococcus lactis

Abstract: The conjugative plasmid pTR2030 has been used extensively to confer phage resistance in commercial Lactococcus starter cultures. The plasmid harbors a 16-kb region, flanked by insertion sequence (IS) elements, that encodes the restriction/modification system LlaI and carries an abortive infection gene, abiA. The AbiA system inhibits both prolate and small isometric phages by interfering with the early stages of phage DNA replication. However, abiA alone does not account for the full abortive activity reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
79
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(80 citation statements)
references
References 55 publications
0
79
0
1
Order By: Relevance
“…Abi systems often are highly toxic when activated; they have varied targets and can act on central cellular processes to inhibit phage DNA replication, transcription, and protein synthesis (9). Specific effects include premature cell lysis by AbiZ (13) and interference of a phage RuvC-like endonuclease by AbiD1 (14).…”
mentioning
confidence: 99%
“…Abi systems often are highly toxic when activated; they have varied targets and can act on central cellular processes to inhibit phage DNA replication, transcription, and protein synthesis (9). Specific effects include premature cell lysis by AbiZ (13) and interference of a phage RuvC-like endonuclease by AbiD1 (14).…”
mentioning
confidence: 99%
“…The most likely explanation for this phenomenon is that Abi proteins interfere with processes essential not only for phage, but also for bacterial development; therefore, death of individual bacterial cells is always observed following activation of the Abi systems [17,[58][59]. As a consequence, release of progeny particles is limited and the bacterial population survives.…”
Section: Phage Abortive Infection Systemsmentioning
confidence: 99%
“…Based on this observation, it was concluded that the AbiV system arrests the bacterial translation apparatus [60]. AbiE, AbiI, AbiQ and AbiZ systems affect maturation of phage particles [59,65]. The AbiZ system, identified in 2007 by Durmaz and Klaenhammer, induces premature lysis of phage-infected cells, resulting in the release of the developing phage particles before completion of the maturation process.…”
Section: Phage Abortive Infection Systemsmentioning
confidence: 99%
See 2 more Smart Citations